Interaksi Obat-Herbal dengan Agen Hormon dalam Terapi Kanker: Tinjauan Mekanisme dan Implikasi Klinis - Zulqifli, Iqbal; Hikmah, Nurul; Shella, Tasya Permata; Azizah, Nabilla Faoziyyah; Apriani, Risa Dwi; Putri, Mukarromah Dita; Hilmi , Indah Laily (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Hormone therapy is the cornerstone of treatment for hormone-dependent cancers, such as breast and prostate cancer. On the other hand, the high rate of herbal medicine use as complementary treatment in cancer patients has the potential to cause herbal drug interactions (HDIs), which can affect the efficacy and safety of the primary therapy. This study aims to identify and categorize drug-herbal interactions (DHIs) in cancer hormone therapy based on pharmacokinetic mechanisms (including CYP450 enzyme and drug transporter modulation) and pharmacodynamic mechanisms (including hormone receptor and signaling pathway modulation), as well as to conclude their clinical implications. A systematic review was conducted following the PRISMA-ScR guidelines. A literature search was performed in the PubMed, Scopus, ScienceDirect, Frontiers, and Google Scholar databases for relevant in silico, in vitro, and in vivo studies published between 2015 and 2025. Analysis showed that HDI can be categorized into two main groups. First, pharmacokinetic interactions that occur through the modulation of cytochrome P450 (CYP) enzymes and drug transporters, such as the reduction in the bioavailability of tamoxifen by Hedyotis diffusa. Second, pharmacodynamic interactions at hormone receptors, such as the synergistic effect between Boswellia serrata and enzalutamide. The nature of interactions varies greatly, from antagonistic to synergistic, depending on the specific herbal-drug pair. These findings emphasize the importance of clinical vigilance, such as open communication with patients, dose adjustments, therapeutic monitoring, and interprofessional collaboration. These measures are necessary to reduce the risk of HDI and improve the efficacy of cancer therapy.